Combination Immunotherapy Use and Withdrawal in Pediatric Inflammatory Bowel Disease-A Review of the Evidence - Joseph Meredith; Joseph Meredith; Paul Henderson; Paul Henderson; David C. Wilson; David C. Wilson; Richard K. Russell; Richard K. Russell (Frontiers Media S.A., 2021)
Evidence-based guidelines have been developed outlining the concomitant use of anti-tumor necrosis factor alpha (anti-TNF) agents and immunomodulators including azathioprine (AZA) and methotrexate (MTX) in both adult and pediatric populations. However, there exists a paucity of data guiding evidence-based strategies for their withdrawal in pediatric patients in sustained remission. This narrative review focuses on the available pediatric evidence on this question in the context of what is known from the larger body of evidence available from adult studies. The objective is to provide clarity and practical guidance around who, what, when, and how to step down pediatric patients with inflammatory bowel disease (IBD) from combination immunotherapy. Outcomes following withdrawal of either of the two most commonly used anti-TNF therapies [infliximab (IFX) or adalimumab (ADA)], or immunomodulator therapies, from a combination regimen are examined. Essentially, a judicious approach must be taken to identify a significant minority of patients who would benefit from treatment rationalization. We conclude that step-down to anti-TNF (rather than immunomodulator) monotherapy after at least 6 months of sustained clinical remission is a viable option for a select group of pediatric patients. This group includes those with good indicators of mucosal healing, low or undetectable anti-TNF trough levels, lack of predictors for severe disease, and no prior escalation of anti-TNF therapy. Transmural healing and specific human leukocyte antigen (HLA) typing are some of the emerging targets and tools that may help facilitate improved outcomes in this process. We also propose a simplified evidence-based schema that may assist in this decision-making process. Further pediatric clinical studies are required to develop the evidence base for decision-making in this area.